“MANAGING CHANGE THROUGH FOSTERING EMPLOYEE INVOLVEMENT” - Sharma, Heena (International Journal of Psychosocial Rehabilitation, 2020)
The employees in today’s scenario have a powerful impulse of getting involved in taking decisions which may influence them. They are getting more and more confident about their knowledge regarding the crucial operational issues and they also wish for contributing their insights. The organizationsrequire to establish mechanisms for taking advantage of unique skills, creativity and talent which could be of much value when allowed to be conveyed. Involvement of employees in decision-making aids the individuals who are involved, to interpret the situation, persuades them that the organizational leaders are not making an effort to double-cross them, and alsoguarantees the utilization of inputs of the parties making efforts to execute and accept the changes undertaken. The purpose of this study is to explore the role played by EI in managing change. Possibly the best way to commence with the understanding that why the establishments require to work more towards ensuring the involvement of their employees in implementing changes is to examine the failure of change efforts. Hence, firstly this study focusses on the factors contributing to change failures. Secondly, this study focusses on establishing the EI as a means for ensuring successful change efforts.